Microleakage Evaluation of Glass Hybrid Restoration Following Usage of Papain-Based Gel and Ceramic Bur for Caries Removal: An In Vitro Study - Halah Abdulkareem A Alkhawaja; Aseel Haidar M.J Al Haidar (Wolters Kluwer Medknow Publications, 2022)
Introduction: In the field of pediatric dentistry, an urge to adopt a more comfortable, minimally invasive, and stressless technique for caries removal became a must. Coronavirus disease-2019 outbreak necessitates a paradigm change in the global health care protocols, requiring alternative, nonaerosol generating approaches. This study aimed to measure and compare the influence of two methods of caries removal, namely, Brix3000 and CeraBur, on the microleakage of glass hybrid restorative material. Materials and Methods: Thirty human primary molar teeth with accessible occluso-gingival carious cavitation were randomly allocated into CeraBur and Brix3000 groups. After selective caries excavation, samples were restored with Equia Forte HT, thermocycled, dipped in thiazine dye, washed, and sectioned through the restoration center. Then microleakage was measured using a stereomicroscope (30× magnification) at both occlusal and gingival margins. Results: No statistically significant difference was found between the two methods of caries removal (CeraBur and Brix3000) at both occlusal (P = 1.000) and gingival margins (P = 0.612). Conclusions: Brix3000 caries removing gel did not negatively affect the microleakage of Equia Forte HT compared to the CeraBur and hence can be used alternatively to the conventional drilling methods.